Interactive Media Development Using Microsoft Sway in Elementary Level Learning Circle - M Gita Primaniarta; Wiryanto Wiryanto (EduMa: Mathematics education learning and teaching, 2022)
Education process and technology go hand in hand and adapt to each other for teachers in carrying out their duties. The Microsoft sway application is the best choice for learning materials for students when carrying out distance learning (PJJ). By office 365 account, teachers can develop learning materials designed with existing Microsoft Sway features. There are titles, text, videos, images that are integrated directly with the internet network. Microsoft Sway is a website-based application that provides more interesting, interactive, online learning content and is integrated with the LMS (Learning Management System). The sway application design is designed with the Deck and Lou Carey development model. The development stage starts with planning, design, and development. The resulting validation shows a value of 95.55% on learning materials assessed by experts in the field of mathematics the media expert validation shows a value of 93.33% assessed by experts in Educational technology. Furthermore, student trials with a questionnaire model showed 84.59% very well in learning media, So the score obtained shows that the learning media using Microsoft Sway is feasible for students to use